INVESTIGATION OF THE EFFECTS OF JUGLONE AND CISPLATIN ON BREAST CANCER CELL LINES - Selda Şimşek; Buket Er Urgancı; Sacide Çakal (International Journal of Health Services Research and Policy)
Breast cancer is one of the most commonly diagnosed malignancies worldwide, accounting for approximately 11% of all cancer-related deaths. Cisplatin induces DNA damage, thereby leading to apoptotic cell death, while juglone, a phytochemical compound, exhibits antioxidant and antiproliferative properties. BLACAT1, miR-155-5p, and CCR2 are non-coding RNAs implicated in breast cancer metastasis. This study aimed to investigate the effects of juglone and cisplatin on breast cancer cells by evaluating their impact on cell viability, gene expression, and invasive potential. MDA-MB-231 and MCF-7 breast cancer cell lines were treated with juglone and cisplatin. Cytotoxic effects were determined using the CCK-8 assay, while qPCR was employed to analyze changes in the expression levels of BLACAT1, miR-155-5p, and CCR2. The impact on cell invasion was assessed using the Transwell invasion assay. Juglone and cisplatin exhibited dose-dependent cytotoxicity in both cell lines. qPCR analysis revealed significant alterations in the expression levels of BLACAT1, miR-155-5p, and CCR2 following treatment. The Transwell invasion assay demonstrated that juglone and cisplatin affected the invasive potential of breast cancer cells, with notable differences observed between individual and combined treatments. Juglone and cisplatin modulate breast cancer cell viability, gene expression, and invasive behavior, with juglone demonstrating potential as a therapeutic agent, particularly for luminal-type breast cancer. However, the combined application did not enhance the therapeutic effect, suggesting a complex interaction between these agents.